Technology Mediated Instruction and its Effect on Cognitive Scaffolding, motivation and Academic Performance in EFL Context - Sepideh Berenji; Mahnaz Saeidi (Journal of English Language Pedagogy and Practice, 2017)
Technology mediated learning brings together the users with shared interests. This method makes learners informally engaged in language learning. This study intended to investigate the effect of technology mediated instruction on cognitive scaffolding, academic performance and motivation. Employing a quasi-experimental research, 80 learners from two intact classes at Islamic Azad University, Osku Branch were selected as the experimental and control groups. Telegram as a tool was used in the experimental group, while the control group received traditional way of instruction. Critical ethnography approach was implemented to consider the amount of cognitive scaffolding. To measure the students’ motivational level in both groups, Course Interest Survey (CIS) was administered at the end of the semester. The total average score for each group was calculated. To compare students’ academic achievement, their average scores in the final academic test were considered. An Independent samples t-test in was used to compare the mean scores. The results indicated that technology mediated learning brought about cognitive scaffolding and the students in the experimental group outperformed the control group in terms of motivation and academic achievement. The results of the study suggest that to bring about academically successful students, practitioners should use technology mediated instruction.